A study on the marketing problems and prospects of Ramlee & Co ( licensed taxation accountant ) in the Kota Kinabalu region / Abdul Rahman Mohsin Bledram - Mohsin Bledram, Abdul Rahman (1992)
This is a brief study on the marketing problems and prospects-of Ramlee & Co (Licensed Taxation Accountant) in the Kota Kinabalu Region. The objectives of this study are to look into the marketing problems and prospects faced by Ramlee & Co in the Kota Kinabalu Region in relation to the marketing mix example price, products, place and promotion and recommend appropriate solutions onto the marketing problems. Besides that, is to identify and analyse the marketing prospects which include determine the potential target markets and exploring the market opportunities available and recommend appropriate marketing strategies in order to increase the company's clients. In obtaining the information for this study, I have done personal interview with the Dewan Perniagaan Bumiputra Sabah, Persatuan Penjaja-Penjaja Kecil Bumiputra Sabah, Inland Revenue Department and the clients of Ramlee & Co especially whom are located in the Kota Kinabalu Region.